Meningkatkan Perkembangan Kognitif Anak melalui Kegiatan Pembelajaran Terintegrasi STEAM (Science, Technology, Engineering, Art, and Mathematics): Improving Children's Cognitive Development through Integrated STEAM (Science, Technology, Engineering, Art, and Mathematics) Learning Activities - Fanny, Novita; Helnita, Helnita; Hayati, Fitriah (Absorbent Mind, 2023)
Cognitive development is the interaction of human maturity with environmental influences. This research aims to improve children's cognitive development through STEAM (Science, Technology, Engineering, Art, and Mathematics) Integrated Learning Activities so that it can become a reference for PAUD institutions. This classroom action research used qualitative methods involving 20 children aged 5-6 years. Data is collected through children's performance and observation sheets. Data analysis was carried out through qualitative descriptive techniques using percentage formulas. The results of research in cycle 1 showed that children's cognitive development was still low, with details of developing very well (BSB) in 1 child (5%), developing as expected (BSH) in 7 children (35%) starting to develop (MB) 9 children (45 %) and not yet developed (BB) to 3 children (15%). Based on these results, planning for cycle II was carried out with improvements including the game tools used and learning media. The results obtained in cycle II were better than cycle I with details: developing very well (BSB) 10 children (50%) developing as expected (BSH) 8 children (40%), starting to develop (MB) 2 children (10%). Based on this data, it shows that STEAM integrated learning can improve children's cognitive development.